PROFIL KADAR SOLUBLE UROKINASE PLASMINOGEN ACTIVATOR RECEPTOR (suPAR) PADA SERUM PENDERITA TUBERKULOSIS PARU (SEBAGAI MONITORING TERAPI) - Astuti, Triwahju; MR, Tri Yudani; Riawan, Wibi; Muktiati, Nunuk Sri; Widjajanto, Edy (Fakultas Kedokteran Universitas Brawijaya, 2008)
Dutch study shows that Upar expression content is significantly higher in tubercolusis patient’s psiphsy monosit compared to those in the healthy control group. So far, there is no biologic marker used whichcan accurately observe response improvement in the treatment of lung tubercolusis. The aim of this research is to investigate whether the serum level of soluble utokinase plasminogen activator receptor (suPAR) carries information in monitoring TB treatment for Lung Tuberculosis patients. suPAR was measured by ELISA in 21 individuals at the time of enrolment into observational cross sectional based on active tuberculosis and 5 individuals as healthy control. There were 3 groups, 1). patients who had not started treatment (n=7),2). patients who had been treated for 2 months (n=7), 3). patients who had been treated for 6 months (n=7). Among groups, there were no difference in mean of body mass index, erythrocyte sedimentation rate and monocyte count. Patients positive for TB on direct microscopy were 29% ( 6 from 21 patients) , 2 patients each groups. The suPAR levels were elevated in patients with active TB compared to healthy control (P<0,001). suPAR levels were highest in patients positive for TB on direct microscopy ( mean suPAR 4.455 ng/ml).